Electrocatalytic water oxidation by a molecular cobalt complex through a high valent cobalt oxo intermediate - Das, Debasree; Pattanayak, Santanu; Singh, Kundan K.; Garai, Bikash; Sen Gupta, Sayam (Chemical Communications, 2016)
Biuret-modified tetraamidomacrocyclic cobalt complex [Co-III-bTAML]- is shown to catalyze electrochemical water oxidation at basic pH leading to the formation of O-2. Electrochemical and spectroscopic studies indicate a high valent cobalt oxo intermediate isoelectronic to Co-V(O) as the active oxidant. The kinetic isotope effect of 8.63 indicates an atom proton transfer mechanism.

Various types of separation membranes - Das, Debasree; Datta, Anindya; Contractor, Aliasgar Qutub (Current Science, 2016)
Membrane-based separation is a superior alternative to conventional processes in many separation problems of practical importance. For maximum effectiveness, both high selectivity and flux are desirable. This article summarizes the global efforts at designing new membrane materials, particularly carbon nanotube (CNT)-based membranes, to achieve the twin objectives mentioned above. Interest in CNT emanates from the excellent transport property of molecules through its frictionless smooth walls, with/without functionalization at the end tips. Permeation of water through graphene oxide (GO) channels, which are otherwise impermeable to solutes, has also generated considerable interest, and GO is being viewed as a promising material for separations. The performances of conducting polymers like polypyrrole, polyaniline, polythiophene-3, 4-ethylenedioxythiophene and their different composites have been studied as a function of changes in morphology and redox behaviour, and this aspect too is covered in the present article. Also, the dependence of the separation performances based on the size, charge and hydrophobic/hydrophilic properties has been discussed in detail. Advances in understanding will have an important bearing on future developments in separation science.
Keywords: carbon nanotube; conducting polymers; flux; graphene oxide; permeability; separation membranes

Versatile Cu-II metal-organic framework exhibiting high gas storage capacity with selectivity for CO2: conversion of CO2 to cyclic carbonate and other catalytic abilities - De, Dinesh; Pal, Tapan K.; Neogi, Subhadip; Senthilkumar, S.; Das, Debasree; Sen Gupta, Sayam; Bharadwaj, Parimal K. (Chemistry-A European Journal, 2016)
A linear tetracarboxylic acid ligand, H4L, with a pendent amine moiety solvothermally forms two isostructural metal-organic frameworks (MOFs) L-M (M=Zn-II, Cu-II). Framework L-Cu can also be obtained from L-Zn by post- synthetic metathesis without losing crystallinity. Compared with L-Zn, the L-Cu framework exhibits high thermal stability and allows removal of guest solvent and metal-bound water molecules to afford the highly porous, L-Cu. At 77K, L-Cu absorbs 2.57wt% of H-2 at 1bar, which increases significantly to 4.67wt% at 36bar. The framework absorbs substantially high amounts of methane (238.38cm(3)g(-1), 17.03wt%) at 303K and 60bar. The CH4 absorption at 303K gives a total volumetric capacity of 166cm(3)(STP)cm(-3) at 35bar (223.25cm(3)g(-1), 15.95wt%). Interestingly, the NH2 groups in the linker, which decorate the channel surface, allow a remarkable 39.0wt% of CO2 to be absorbed at 1bar and 273K, which comes within the dominion of the most famous MOFs for CO2 absorption. Also, L-Cu shows pronounced selectivity for CO2 absorption over CH4, N-2, and H-2 at 273K. The absorbed CO2 can be converted to value-added cyclic carbonates under relatively mild reaction conditions (20bar, 120 degrees C). Finally, L-Cu is found to be an excellent heterogeneous catalyst in regioselective 1,3-dipolar cycloaddition reactions (click reactions) and provides an efficient, economic route for the one-pot synthesis of structurally divergent propargylamines through three-component coupling of alkynes, amines, and aldehydes.
Keywords: click reactions; CO2 absorption; cyclic carbonate; heterogeneous catalysis; metal-organic frameworks

Porphyrin-based conducting polymer hydrogel for supercapacitor application - Das, Debasree; Kurungot, Sreekumar (Energy Technology, 2020)
Herein, the electrochemical properties and energy storage capability of a flexible, all-solid-state supercapacitor based on the supramolecular assembly of polypyrrole (PPy) and the anion of 5,10,15,20-tetrakis(4-sulfonatophenyl)-21H,23H-porphine manganese(III) chloride (MnTSPP) are reported. The electrode material consists of a conductive polymer hydrogel formed through the gelation initiated by cross-linking of the dopant MnTSPP anion in the PPy chains. The morphology of the cross-linked polymer hydrogel is that of a particle-decorated nanofiber, which can perform as a flexible supercapacitor electrode material with a specific capacitance of 300 Fg(-1) and capacitance retention of 78% up to 10 000 cycles. The anion of MnTSPP plays a pivotal role in enhancing the charge storage capability by facilitating the electron transfer between the polymer interchains. In addition, the steric hindrance due to the large size of the dopant counter ions of MnTSPP reduces the counterion drain effect and structural pulverization of PPy, thereby improving the capacitive retention.
Keywords: conductive hydrogels; energy storage devices; Flexible Supercapacitors; nanofibers; porphyrin-based polymers

Electrocatalytic alcohol oxidation by a molecular iron complex - Kuiry, Himangshu; Das, Debasree; Das, Soumadip; Chakraborty, Soham; Chandra, Bittu; Sen Gupta, Sayam (Faraday Discussions, 2022)
An efficient electrochemical method for the selective oxidation of alcohols to their corresponding aldehydes/ketones using a biomimetic iron complex, [(bTAML)Fe-III-OH2](-), as the redox mediator in an undivided electrochemical cell with inexpensive carbon and nickel electrodes using water as an oxygen source is reported. The substrate scope also includes alcohols that contain O and N heteroatoms in the scaffold, which are well tolerated under these reaction conditions. Mechanistic studies show the involvement of a high-valent Fe-V(O) species, [(bTAML)Fe-V(O)](-), formed via PCET (overall 2H(+)/2e(-)) from [(bTAML)Fe-III-OH2](-) at 0.77 V (vs. Fc(+)/Fc). Moreover, electrokinetic studies of the oxidation of C-H bonds indicate a second-order reaction, with the C-H abstraction by Fe-V(O) being the rate-determining step. The overall mechanism, studied using linear free energy relationships and radical clocks, indicates a ``net hydride'' transfer, leading to the oxidation of the alcohol to the corresponding aldehyde or ketone. When the reaction was carried out at pH > 11, the reaction could be carried out at a similar to 500 mV lower potential than that at pH 8, albeit with reduced reaction rates. The reactive intermediate involved at pH > 11 is the corresponding one-electron oxidized [(bTAML)Fe-IV(O)](2-) species.